Differential response of potato cultivars intended for the processing industry - GALDINO, Antonia Gorete da Silva; PEREIRA, Ariana Mota; GUIMARÃES, Maria Eduarda da Silva; ARAÚJO, Nícolas Oliveira de; AMORIM, Francisca Frenna Verezza Rodrigues de; FINGER, Fernando Luiz; GOMES, Mateus de Paula (Food Science and Technology, 2023)
The choice of a cultivar has been the main limitation for the potato processing industry, with low availability of genotypes with adequate shape and size for slicing, absence of non-enzymatic browning after frying, and good storage potential, which is evaluated mainly by the incidence of sprouts. Therefore, the objective of this study was to evaluate the potential of 10 cultivars in the pre-fried potato processing industry over a period of up to 180 days of storage at 8°C. Analyses of accumulated mass loss (AML), sprouting, alcohol insoluble solids (AIS), total soluble sugars (TSS), non-reducing sugars (NRS), reducing sugars (RS), and visual staining and colorimetry (L* and b*) were performed after frying. The cultivar Basin Russet presents lower values for AML. The cvs. Innovator and Umatilla Russet were the cultivars that showed later sprouting, and at 180 days, Umatilla Russet had smaller shoots. The AIS levels did not correlate with sprouting and sugar content. The TSS and NRS varied among the cultivars, and the RS contents were in the range of 0.005–0.206%, with Ranger Russet, Russet Burbank, Umatilla Russet, and Yona showing values above 0.12%, which was considered high when compared to the other cultivars. All cultivars were visually classified in category 2 or 3 for the USDA fry color chart. However, through the L* variable, the cultivars Alverstone Russet and Basin Russet presented sticks with a lighter color and the “Challenger” with a more yellowish hue. L* values above 64.1 and b* values above 50.3 are indicated for the evaluated cultivars. It is concluded that among the evaluated cultivars, the best variables for the pre-fried potato processing industry were obtained in the Innovator, Alverstone Russet, and Basin Russet cultivars.